Efeito da música no alívio da dor durante o banho no leito no pós-operatório de cirurgia cardíaca: ensaio clínico randomizado - Sarmento, Sabrina Daiane Gurgel (2022)
A frequent complication reported by patients in the postoperative period of cardiac surgery is pain, therefore, this event can be mitigated through pharmacological and non-pharmacological therapies. The latter includes music as a non-pharmacological alternative to minimize the patient's pain. Thus, the present study aims to evaluate the effect of music on pain relief during bed bath of patients in the immediate postoperative period of cardiac surgery. This is a randomized and controlled clinical trial that was carried out in the Intensive Care Unit (ICU) of a hospital in the state of Rio Grande do Norte. The sample group consisted of 38 patients undergoing cardiac surgery for myocardial revascularization, divided into a Control Group (CG) and Experimental Group (EG), where the EG received the intervention with headphones with sound of their choice, while the GC, only headphones without sound, during the first postsurgery bed bath. As for data collection, the main researcher performed the randomization and applied the headphone in both groups, during the bed bath, then the second researcher applied the assessment instrument before, during and ten minutes after the bed bath. Finally, the main researcher removed the headphone, thus guaranteeing the ignorance of the second researcher of the group to which the patient belonged, being the researcher of the blind type. This project was submitted to the Research Ethics Committee of HUOL and approved under registration 3.425.285 and CAAE: 11745419.6.0000.5292 and registered in the Brazilian Registry of Clinical Trials (RBR-69w6f5z). The present investigation was distributed according to randomization in 52.26% of the CG and 44.74% of the EG. Regarding the socioepidemiological profile, it was observed that there was no statistical difference when comparing the studied groups (p<0.05) revealing a homogeneity in the studied groups, demonstrating in total that 81.58% of the patients were male, 60.53 % aged up to 64 years, 65.79% were married and 44.74% had elementary education. Regarding the variables related to the intervention instrument of the study, they showed that 86.84% used to listen to music, with a preference for gospel songs and Brazilian popular music. When comparing its effect during the bed bath between the CG and EG, it was observed that there was significance (p<0.05%) in the reduction of pain verified by the numerical scale of pain and Wong Baker faces at the moment during and after bathing in the bed for the EG, revealing an important reduction of 2.41 points for those who listened to music. When comparing vital signs, it was observed that within the EG there was a reduction in heart rate (p=0.019); while for the CG pain had high scores before, during and after, although there was a small reduction, in relation to vital signs, blood pressure had a higher percentage of normal pressure level for the CG (p=0.018). Music reduced the patient's pain during a nursing procedure in patients in the postoperative period of myocardial revascularization surgery, being a simple and easy-to-handle tool that should be valued and applied by the nursing team, ensuring a humanized nursing care and of quality.